Posttraumatic stress disorder in patients after transient ischemic attack: A one-year follow-up - Utz, Kathrin S.; Kiphuth, Ines C.; Schenk, Thomas (Journal of psychosomatic research, 2019)
Objective: We aimed to determine the prevalence of posttraumatic stress disorder (PTSD) 12 months after transient ischemic attack (TIA). Method: TIA patients of our previous investigation (examined 3 months after the event) were again examined 12 months after the diagnosis. PTSD and associated variables were assessed via self-rating instruments. Results: Eighty-four patients were included in the analyses. Twelve months after TIA the prevalence of probable PTSD was reduced (8.3%) compared to that found 3 months after TIA (29.6%). Coping assessed 3 months after TIA predicted long-term PTSD severity. Conclusion: Although the prevalence of probable PTSD decreased 12 months after experiencing a TIA compared to 3 months after TIA, prevalence of probable PTSD is still increased relative to that in the general population.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Coping; Posttraumatic stress disorder; Quality of life; Transient ischemic attack